Inequality and Trust: Some Inequalities are More Harmful than Others - Magnus Gustavsson; Henrik Jordahl (Uppsala University, Department of Economics, 2006)
We present new evidence on the influence of income inequality on generalized trust. Using individual panel data from Swedish counties together with an instrumental variable strategy we find that differences in disposable income, and especially differences among people in the bottom half of the income distribution, are associated with lower trust. The relationship between income inequality and trust is particularly strong for people with a strong aversion against income differentials. We also find that the proportion of people born in a foreign country is negatively associated with trust.
urn:nbn:se:uu:diva-210884
Keywords: C23; D31; Z13; 330; trust; social capital; inequality; Vertrauen; Einkommensverteilung; Social Capital; Sozialpsychologie; Schweden